Evaluation of Serum Ferritin Levels in Patients of Hypothyroidism - Vartika Saini; Sunny Chopra; Jaspinder Kaur; Maninder Kaur (Indian Journal of Medical Biochemistry)
Background: The thyroid gland is a bilobed endocrine gland that secretes two vital hormones: thyroxine (T4) and triiodothyronine (T3). The production and release of these hormones are regulated by the thyroid-stimulating hormone (TSH) from the pituitary gland. Iron is an essential element for the normal functioning of the thyroid gland. In the body, iron is stored in the form of ferritin, an intracellular protein. The aim of the present study was to evaluate the serum ferritin levels in patients with hypothyroidism. Materials and methods: This case-control study was conducted on 100 lab-diagnosed cases based on the thyroid profile. About 50 healthy controls were included in the study. Thyroid profile which includes estimation of serum T3, T4, and TSH was done. Serum ferritin levels were also estimated in both cases and controls. Results: The mean ± SD value of serum TSH levels in study group and control group was 14.45 ± 12.96 µIU/mL and 1.27 ± 1.05 µIU/mL, respectively. The mean ± SD of Serum ferritin in study group and control group was 9.95 ± 6.36 ng/mL and 149.35 ± 103.16 ng/mL, respectively. Serum ferritin and TSH shows significant (p-value ≤ 0.001). A significant negative correlation was found between TSH and serum ferritin in hypothyroid patients. Conclusion: This suggests that hypothyroid patients had higher levels of TSH and lower levels of serum ferritin compared to the control group, and that there is a negative correlation between TSH and serum ferritin in hypothyroid patients. Hence, the estimation of serum ferritin concentration among hypothyroid patients could be useful in the evaluation of thyroid hormone status.